KESULITAN BELAJAR MYOB ACCOUNTING PADA SISWA KELAS XII AKUNTANSI 2 SMKN 1 PONTIANAK - Ahmad Rosyadi; Warneri Warneri; Okianna Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractThis study aims to determine the causes of learning difficulties students on learning myob accounting on students in XII class of SMKN 1 Pontianak. The method used in this research is qualitative research approach method. Sources of data in this study are all students in XII Class Accounting 2 of SMKN 1 Pontianak who was not pass the score. There were 13 students. Data collection techniques are direct observation techniques, direct communication and documentary study techniques. While the data collection tool are the interview guide, the observation sheet (check list). Data processing techniques using domain analysis techniques. The results of the findings based on observation and interview data were analyzed and it was concluded that the cause of students' learning difficulties in learning MYOB accounting is from internal factors with the following aspects: (1) Learning Attention, (2) Readiness Learning. Based on appendix 7 overall the average internal factor score of 3.16 is categorized as less well, and which becomes dominant affecting students' learning difficulties lies in poorly categorized. Keywords: Student Learning Difficulties, MYOB Accounting, Students